Documenting limited health literacy in a clinical setting - Julie Nguyen; Caitlyn McNaughton; Jessica Sautter (Elsevier, 2022)
Objective: Health literacy is important in lung cancer care, where treatments and symptoms are difficult to navigate. This study aims to describe how a single-item measure of health literacy can facilitate health literacy system capacity. Methods: Data include retrospective medical records from 456 patients with lung cancer. Limited or adequate health literacy was based on participant response to the Single Item Literacy Screener (SILS). Data were collected over a 12-month period following diagnosis for each patient. Results: One-third of patients had limited health literacy; they were more likely to have lung cancers of stage IIIB or higher and greater median levels of depression based on the PHQ-9 questionnaire. Patients with limited health literacy were also more likely to have at least one emergency department visit or unplanned hospitalization and had these visits sooner. Conclusion: These data document need for interventions to buffer the association between limited health literacy and poor health outcomes. Innovation: Routine intake screens should include the SILS to measure health literacy among lung cancer patients. New models that address health literacy at the organizational and patient levels can be implemented in health care settings using the SILS.